Profitabilitas, Kecukupan Modal, Leverage dan Nilai Perusahaan dengan Pengungkapan Islamic Social Reporting sebagai Variabel Moderating - Tunjungsari, Septi; Irkhami, Nafis (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
The purpose of this study was to determine the effect of profitability, capital adequacy, and leverage on firm value with Islamic Social Reporting (ISR) as a moderating variable. The population of this research data is BUS in Indonesia for the period 2014-2019. The sampling method is purposive sampling, which uses several criteria so that there are 11 BUS as the research sample. The data were processed using multiple linear regression with the help of Eviews 10. The results showed that ROA had a significant positive effect on firm value, while ROE had a significant negative effect on firm value. CAR and leverage have no significant effect on firm value. ISR is not able to moderate CAR and leverage to firm value, while ROA and ROE are able to moderate ISR to firm value.   Keywords: Profitability; ROA; ROE; CAR; Leverage; ISR.